The effect of behavioral parent training on decreasing stress and improving parenting styles of mothers of children with externalized behavior problems - Mohsen Amiri; Reza Pourhosein; Majid Yosefi Afrashteh; Mahdi Khanabadi; Abbas Motavallipor (مجله علوم روانشناختی, 2015)
Parental stress and psychological problems of parents of children with behavioral problems have devastating effects on parents' reports of their parenting style and welfare and hence is one of the ways to improve this problems is offering psychological training to parents in the  field of controling children with behavioral problems. Therefore, the purpose of the current study was to investigate the effect of training behavior modification methods on mothers of children with externalized behavior problems on reducing stress and improving parenting styles of these mothers. The research method was quasi-experimental with pre-test and post-test design and a control group. 24 mothers of children with externalized behavior problems were selected using at-hand sampling and divided into control and experimental groups. Both groups filled out  child behavior checklist, parenting style scale and parenting stress index. For the next step, the experimental group received instructions on behavior modification methods in 9 ninety-minute sessions while the mothers in control group went on their normal tasks. At the end of the instructional session, both groups filled out the mentioned questioners as the post-test. Covariance analysis was used for analyzing data. The results of the analysis of covariance showed that instructing behavior modification methods improved authoritarian parenting style scores in mothers (P<0/05) and also decreased authoritative and neglectful parenting practices scores parenting stress (P<0/05) among mothers in experimental group, in comparison with the control group. The results showed that offering behavioral training to mothers improves their parenting style and prevents rising confusion in parent-child relationships and also emotional problems in mothers of children with externalized behavior problems.